Flupyradifurone Exhibits Greater Toxicity to the Asian Bumblebee Bombus lantschouensis Compared to the European Bumblebee Bombus terrestris - Chunting Jie; Hong Zhang; Ziyu Zhou; Zhengying Miao; Bo Han; Baodi Guo; Yi Guo; Xiao Hu; Shahid Iqbal; Bingshuai Wei; Jiaxing Huang; Pingli Dai; et al. (Insects)
Pesticides are considered a major factor in the decline of bee populations. Flupyradifurone, a novel insecticide, is believed to be relatively ‘bee-safe’. This study aims to evaluate the acute and chronic toxicity of flupyradifurone and assess its risks to both commercial bumblebee Bombus terrestris and the Asian native species B. lantschouensis. Oral toxicity tests demonstrated species-specific sensitivity, with B. lantschouensis exhibiting 5.4-fold higher acute toxicity (72-h LD50: 5.1 μg/bee vs. 28 μg/bee) and 3-fold lower chronic toxicity (No Observed Adverse Effect Concentration, NOAEC: 20 μg/mL vs. 60 μg/mL) compared to B. terrestris. Risk assessments indicated low Hazard Quotients (HQ) of 4 for B. terrestris and 20 for B. lantschouensis. However, the Exposure Toxicity Ratio (ETR) values from both screening and first-tier assessments exceeded the trigger levels, necessitating further testing. This study provides crucial data on the acute and chronic toxic effects of flupyradifurone and highlights the need for more comprehensive insecticide risk assessments, particularly for non-Apis pollinators, to better protect these vital species.